The effect of light massage on blood pressure and mean arterial pressure in tuberculosis patients - Awaludin, Sidik; Sumeru, Annas; Swasti, KG (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4416, 2021)
Tuberculosis is still a significant problem in the health sector, including the side effects of its treatment. Side effects include indigestion, nausea, joint pain, dizziness, reddish urine, itching, redness of the skin, liver disorders, joint pain, and vascular disorders such as paresthesia and even hypertension. Light massage is a massage therapy in the form of gentle movements on the soft tissues of the body, including rubbing and rubbing movements. This skin stimulus will provide a sense of comfort, relax tension in muscles and improve blood circulation. This study aimed to determine the effect of light massage therapy on blood pressure and mean atrial pressure (MAP) in tuberculosis patients. This study used a experimental design, pre-post control group design. The sample size of this study was 60 respondents. The sampling technique used was simple random. The results showed that most respondents were female (56.7%) with active phase treatment 76.7% in the intervention group and 73.4% in the control group. There was a significant difference in systolic blood pressure and MAP (p <0.05), and there was no significant difference in diastolic blood pressure between the intervention and control groups (p> 0.05). Light massage can reduce systolic blood pressure and MAP. Further research is needed to increase the duration and frequency of light massage interventions